2008
DOI: 10.1016/j.jneumeth.2008.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microdialysis probes on vasculature and dopamine in the rat striatum: A combined fluorescence and voltammetric study

Abstract: Measuring extracellular dopamine in the brain of living animals by means of microdialysis and/or voltammetry is a route towards understanding both normal brain function and pathology. Previous reports, however, suggest that the tissue response to implantation of devices may affect the outcome of the measurements. To address the source of the tissue response and its impact on striatal dopamine systems microdialysis probes were placed in the striatum of anesthetized rats. Images obtained by dual-label fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 50 publications
3
77
0
Order By: Relevance
“…8. 37 This is evidence that the probes open the BBB. We also found that fluorescent nanobeads used to represent blood flow spill out of blood vessels near microdialysis probes, but not elsewhere in the brain, providing direct evidence that the BBB is opened, as shown in Fig.…”
Section: Immunohistology Of Probe Implantation and Mitigating Damagementioning
confidence: 94%
“…8. 37 This is evidence that the probes open the BBB. We also found that fluorescent nanobeads used to represent blood flow spill out of blood vessels near microdialysis probes, but not elsewhere in the brain, providing direct evidence that the BBB is opened, as shown in Fig.…”
Section: Immunohistology Of Probe Implantation and Mitigating Damagementioning
confidence: 94%
“…The procedures for immunohistochemistry and fluorescence microscopy are described in our previous papers. 32,[48][49] Rats were deeply anesthetized with isoflurane (2.5% by volume O 2 ) and perfused transcardially with 200 ml 0.01 M phosphate-buffered saline (PBS), pH 7.4, followed by 160mL of 4% paraformaldehyde, and then with 50mL of a solution containing commercially available Table 1. The noise in a 10-min baseline prior to each needle prick was used to create a threshold for detection of the glucose dip (see Figure S4 for details).…”
Section: All Procedures Involving Animals Were Approved By the Univermentioning
confidence: 99%
“…The results indicate confusion from tissue damage. (59,60) How can we measure in spaces of nanometer dimensions without destroying the very architecture that determines the problem of interest? Below we present two approaches, both with strengths and weaknesses.…”
Section: Measuring In Vivo Profilesmentioning
confidence: 99%